2000
DOI: 10.1093/ndt/15.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Early recurrent nephrotic syndrome after renal transplantation in children with focal segmental glomerulosclerosis

Abstract: These results support more liberal use of living-related donors for renal transplantation of children with FSGS and ESRD, considering the shortage of cadaveric donors in our society and relatively good efficacy of the early and intensive PE+CPM therapy for early recurrent nephrotic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 18 publications
4
75
0
2
Order By: Relevance
“…Plasmapheresis Plasma-based treatments, primarily plasmapheresis, have been used as a first-line treatment for FSGS and for recurrent FSGS after transplantation for nearly 20 years [5,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The results of select studies performed since the year 2000 with larger numbers of patients are summarized in Table 2.…”
Section: Treatmentmentioning
confidence: 99%
“…Plasmapheresis Plasma-based treatments, primarily plasmapheresis, have been used as a first-line treatment for FSGS and for recurrent FSGS after transplantation for nearly 20 years [5,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The results of select studies performed since the year 2000 with larger numbers of patients are summarized in Table 2.…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, in patients with FSGS the risk of recurrence after kidney transplantation is estimated to be 11%-50%, an event that again leads to terminal renal failure. [2][3][4] The risk for recurrence of FSGS in patients with inherited forms of SRNS is lower than that in patients with nonhereditary FSGS. 5,6 SRNS is one of the most intractable diseases in nephrology.…”
mentioning
confidence: 99%
“…The treatment of FSGS recurrence is uncertain with no available international guidelines; few studies reported beneficial results of plasmapheresis (ranging from 10-23 sessions), with or without rituximab [12]. Moreover, some centres combined plasmapheresis with cyclophosphamide (while the antimetabolite immune suppression transiently discontinued) [13,14]. Both strategies showed promising results with complete or partial remission of FSGS.…”
Section: Discussionmentioning
confidence: 99%